Navigating the landscape of online learning: strengths and weaknesses - Ramli, Abd Rasyid; Wahab, Burhanuddin; Mansor, Ab Razak (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
The growth of online education has presented opportunities as well as challenges. This paper examines the benefits and drawbacks of online learning, incorporating knowledge from current studies to offer a comprehensive picture of this ever-changing educational environment.